Biharmonic (ω, 2ω) ionization of atoms by elliptically-polarized light. Carving the photoelectron angular distributions. (1st October 2022) - Fritzsche, S; Hofbrucker, J
Abstract: The biharmonic ( ω, 2 ω ) photoionization of atomic inner-shell electrons opens up new perspectives for studying nonlinear light–atom interactions at intensities in the transition regime from weak to strong-field physics. In particular, the control of the frequency and polarization of biharmonic beams enables one to carve the photoelectron angular distribution and to enhance the resolution of ionization measurements by the (simultaneous) absorption of photons. Apart from its quite obvious polarization dependence, the photoelectron angular distributions are sensitive also to the (relative) intensity, the phase difference and the temporal structure of the incoming beam components, both at resonant and nonresonant frequencies. Here, we describe and analyze several characteristic features of biharmonic ionization in the framework of second-order perturbation theory and (so-called) ionization pathways, as they are readily derived from the interaction of inner-shell electrons with the electric-dipole field of the incident beam. We show how the photoelectron angular distribution and elliptical dichroism can be shaped in rather an unprecedented way by just tuning the properties of the biharmonic field. Since such fields are nowadays accessible from high-harmonic sources or free-electron lasers, these and further investigations might help extract photoionization amplitudes or the phase difference of incoming beams.